Teaching Primary School Students Reflection on Learning: Opportunities in Lithuanian Language Textbooks - Kulevičienė, Rasa (Acta Paedagogica Vilnensia, 2022)
In Lithuania, the enablement of primary form students to reflect on learning, and especially during lessons of the Lithuanian language, is little investigated. Therefore, this paper discusses what possibilities are provided by student books on the Lithuanian language Taip and Pupa in this process. The method of thematic analysis was used for the analysis of the said student books. The research revealed that student books from the series Taip include high-quality instruments to achieve this aim, i.e., questions for children’s reflections, open-ended sentences, starting from form 1. Even though these elements remain the same in particular forms throughout an entire school year, a teacher can employ them for different purposes. It was also found that high quality instruments included in the Lithuanian language student books Pupa, i.e. questions on reflecting about learning, are introduced respectively from form 2. Like in student books on the Lithuanian language Taip, instruments for particular forms are the same for an entire school year. The research also revealed that instruments presented in student book series on the Lithuanian language Taip and Pupa are highly valuable, as teachers have the possibility to empower school students to reflect on learning during Lithuanian language lessons in many various aspects, such as cognitive, sensitive, and emotional activities, the problem and value of learning, decision-making, etc.
Keywords: primary form students; Lithuanian language; learning; student books; children’s reflections